Ang babaye, banwa kag natiano women's concerns and issues on flooding and their involvement in the disaster risk reduction management plan of Oton, Iloilo. - Redison, Frances Anthea R. (2013.)
The study documents selected women?s concerns and issues on flooding on the three selected flood-prone barangays of Oton, Iloilo and their awareness of, and involvement in, the planning and implementation of the Disaster Risk Reduction Management Plan. There were total of sixty (60) women respondents who are officially registered voters of the three barangays drawn randomly from the local list of voters of the commission on Elections (COMELEC) Master List of Voters. Key informant interviews were used to gather additional information about women?s insights and experiences of flooding, twenty (20) each barangay. Based on the study?s survey, the majority of the women tend to not participate in community affairs because family is still the priority and civic responsibility is seen as optional if not necessary thus reflects or contributes to their limited awareness of the DRRM Plan of Oton. The findings support the need for gender synthesizing before mainstreaming, and recommends the re-organization of women?s groups and promotion of a community-based DRRM which involves inter-barangay alliance ? to give women an avenue to challenge and change their gendered status in society.
Research Paper (Undergraduated, Bachelor of Arts in Political Science-Historty) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2013.
Keywords: Disaster Risk Reduction Management Plan -- Oton, Iloilo -- Research; Women -- Concern and issues -- DRRMP -- Oton, Iloilo -- Research